Head-to-head comparison of the efficacy of Xpert MTB/RIF Ultra and Xpert MTB/RIF for the diagnosis of tuberculous pleurisy: A systematic review and meta-analysis. Issue 20 (20th May 2022) - Yu, Wenfeng; Shen, Yanqin; Zhu, Pengfei; Chen, Da
Abstract: Background: The aim of this study was to evaluate the diagnostic accuracy of Xpert MTB/RIF Ultra (Xpert Ultra) and Xpert MTB/RIF (Xpert) for the diagnosis of tuberculous pleurisy (TBP) head-to-head using meta-analysis method. Methods: On May 12, 2021, we searched multiple databases for reports that used Xpert Ultra and Xpert for TBP diagnosis head-to-head and screened eligible studies for inclusion. Accuracy of Xpert Ultra and Xpert were compared to that of the composite reference standard (CRS) and culture. When heterogeneity was evident, sources of heterogeneity were explored using subgroup analyses, sensitivity analysis, and meta-regression analyses. Results: Five articles met the inclusion criteria for meta-analysis. When results from different specimens or different reference standards were reported in the same article, we analyzed them as separate studies. Thus, 6 studies compared Xpert Ultra and Xpert with CRS, 5 studies compared Xpert Ultra and Xpert with culture. Pooled sensitivity and specificity of Xpert Ultra were 52% and 98% compared to CRS, and 82% and 77% compared to culture. Pooled sensitivity and specificity of Xpert were 22% and 99% compared to CRS, and 48% and 94% compared to culture. Significant heterogeneity in sensitivity was observed compared to CRS. Conclusion: The sensitivity of Xpert Ultra was moderate but better than that of the Xpert; however, its specificity was lower. The role of Xpert Ultra and Xpert in the early and rapid diagnosis of TBP was limited.